Efeitos dos anticoagulantes heparina e NA2EDTA nas análises hematológicas de carpa capim (Ctenopharyngodon idella) - Bagé, Rudi de Carvalho (2017)
The present study evaluated effect of heparin 100 and 5,000 IU, and Na2EDTA at concentrations of 5 and 10%, on blood coagulation and hematological parameters of Grass carp. Twelve fish were used, with a mean weight of 413.75 ± 32.38 g and mean total length of 33.73 ± 0.93 cm, to collect blood samples and determine percentage of hematocrit and hemoglobin and glucose concentration. The data were submitted to analysis of variance, and the means were compared by the Tukey test, at 5% probability. Results indicated that sodium heparin was not efficient for coagulation inhibition and hemolysis occurrence, because it did not conserve samples for a period more than 10 hours. Heparinized blood also showed a significant difference (P> 0.05) in hemoglobin and glucose analyzes, possibly due to coagulation. Plasma with heparin presented a gelatinous appearance after storage at a temperature of 2 to 8 ° C. Therefore, this anticoagulant should be used in rapid hematological procedures but not for further analysis. EDTA presented better results, since there was no significant difference (P> 0.05) in the results of hematocrit, hemoglobin, glucose and for preserving the samples for a longer period of time. However, it is important to note that EDTA control and 5% EDTA treatments showed a slight occurrence of coagulation, with 10% EDTA concentration being the safest. Therefore, Na2EDTA is more recommended for grass carp, since this treatment presented the lowest rate of alterations in stored blood.